Petroleum Fluid Phase Behavior : Characterization, Processes, and Applications - Tewari, Raj Deo; Dandekar, Abhijit Y.; Moreno Ortiz, Jaime; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This book deals with complex fluid characterization of oil and gas reservoirs, emphasizing the importance of PVT parameters for practical application in reservoir simulation and management. It covers modeling of PVT parameters, QA/QC of PVT data from lab studies, EOS modeling, PVT simulation and compositional grading and variation. It describes generation of data for reservoir engineering calculations in view of limited and unreliable data and techniques like downhole fluid analysis and photophysics of reservoir fluids. It discusses behavior of unconventional reservoirs, particularly for difficult resources like shale gas, shale oil, coalbed methane, reservoirs, heavy and extra heavy oils.
1. Reservoir Fluid Properties 2. Fluid Characterization and Recovery Mechanism 3. Advanced Fluid Sampling and Characterization of Complex Hydrocarbon Systems 4. Planning of Laboratory Studies 5. Phase Behavior of Petroleum Reservoir Fluids in the Dense Phase or Supercritical Region 6. Special Characterization for EOR Processes 7. Compositional, Fluid Property, and Phase Behavior Characteristics of Unconventional Reservoir Fluids 8. Porous Media Effects on Phase Behavior of (Unconventional) Petroleum Reservoir Fluids 9. Compositional and Phase Behavior Effects in Conventional and Exotic Heavy Oil EOR Processes 10. Flow Assurance in EOR Design and Operation 11. EOS and PVT Simulations 12. Empirical Relations for Estimating Fluid Properties.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Chemical & Biochemical; TECHNOLOGY & ENGINEERING / Civil / General; coalbed methane; complex fluid characterization; EOR; flow assurance; heavy oil; phase fluids; reservoir engineering; reservoir fluids; shale gas; shale oil; Petroleum -- Migration; Petroleum reserves; Petroleum -- Fluid dynamics; Phase rule and equilibrium; Oil reservoir engineering; Gas reservoirs; Electronic books